Effectiveness of Find Someone Who Method in Improving English Speaking Skills in Lombok Tourism Polytechnic Students - Kufrabawa, Wendi (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to analyze the effectiveness of the "Find Someone Who" method in improving the English-speaking skills of Lombok Tourism Polytechnic (POLTEKPAR) students. It is hoped that this method can provide an innovative alternative in teaching English, especially in the tourism context. Through an experimental research design, two classes with 30 students each were used as samples, where class VIIIA applied the "Find Someone Who" method as the experimental class, while class VIIIB used the conventional method as the control class. Data collection was carried out through speaking tests and analysis of the results showed that the experimental class obtained an average score of 77.1, while the control class only achieved 66.90. The statistical test shows that the calculated t value of 3.31 is greater than the t table of 2.00, so the alternative hypothesis is accepted, which means there is a positive influence of the "Find Someone Who" method on students' speaking skills. These findings emphasize the importance of an interactive learning approach in improving students' verbal communication skills in the tourism sector.